Optimalisasi Penerapan Accurate Online dalam Proses Pencatatan Transaksi Keuangan di Kantor Jasa Akuntan (KJA) - Isti Choiril Mala; Diah Hari Suryaningrum (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze how the implementation of Accurate Online can optimize the financial transaction recording process at a Public Accounting Firm (KJA). The research method used is a descriptive qualitative approach through participatory observation and in-depth interviews with users of Accurate Online during the researcher’s internship. The results indicate that Accurate Online successfully simplifies the recording process—previously scattered across multiple applications—into one centralized and integrated system. The platform also features access control to ensure the security and confidentiality of client data. Implementation challenges such as user adaptation and system transition were addressed through consistent training and usage. Moreover, Accurate Online proves effective in accelerating the preparation of financial reports when transactions are recorded in real-time. This research provides practical contributions for accounting firms and other organizations seeking to optimize their cloud-based accounting systems.